2015
DOI: 10.1039/c5ra04047g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, microstructure and properties of Ti–Al porous intermetallic compounds prepared by a thermal explosion reaction

Abstract: Ti-Al porous intermetallic compounds were prepared by a simple and energy-saving process of thermal explosion (TE) reactions. The effects of the Ti/Al molar ratios (including Ti : Al ¼ 3 : 1, 2 : 1, 1 : 1, 1 : 2 and 1 : 3) on the temperature profiles, phase compositions, pore characteristics, density, expansion behaviors and oxidation resistance were investigated. The ignition temperatures were between 630-653 C and the combustion temperatures were between 737-1161 C, both of which are higher than the target f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 40 publications
0
13
0
2
Order By: Relevance
“…The formation mechanism of intermetallic compound during in-situ processing can be explained by diffusion process 19 or thermal explosion (TE) 20 . Sun et al .…”
Section: Introductionmentioning
confidence: 99%
“…The formation mechanism of intermetallic compound during in-situ processing can be explained by diffusion process 19 or thermal explosion (TE) 20 . Sun et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to mention that the major limitation of these researches is long sintering time and thus present a high energy consumption route. Yet there are researches which reported that the pore formation mechanism of porous Ti-Al materials depends on the thermal explosion (TE) reaction, accompanied by a large amount of heat release [17][18][19]. Contrary to Kirkendall effect, the bulk specimen was ignited by a constant heating rate and the reaction occurred over the whole specimen to the ignition temperature during TE [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TE is a highly exothermic reaction, and hence has the advantage of low energy consumption, simplicity of equipment and short sintering time [3]. Wang et al [19] prepared porous TiAlbased intermetallics via TE with high open porosity of 84%, and the total sintering time only took about 6 h. Porous TiAl 3 intermetallics have the higher oxidation resistance in Ti-Al system, compared to Ti 3 Al and TiAl phases and relative low density [3,18,21]. Shi et al [18] studied the effect of Ti/Al molar ratios on pore structures of porous Ti-Al intermetallics, and the specimen with Ti/Al molar ratio of 1:3 showed excellent high-temperature oxidation resistance at 650°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other approaches have also been developed in order to obtain metallic foams. For example, Shi et al reported the fabrication of porous Ti-Al alloy with thermal explosion (TE) reaction during the sintering [ 27 ]. Another approach that is easy to apply during sintering is in-situ gas release.…”
Section: Introductionmentioning
confidence: 99%